ANALISIS EKONOMI PEMBANGUNAN JALAN DI KECAMATANGISTING KABUPATEN TANGGAMUS MENGGUNAKANMETODE ANALYTICAL HIERARCHY PROCCESS - Adriani, Niken, Drs. Agung Riyardi, M.Si (2017)
Construction of Road Infrastructure is an important element of the system that can sustain the economy sector in the region. This research aims to know the order of priority criteria in the economic analysis of road construction. This research uses three (3) criteria : Economic Acceleration, Economic Expansion, Socio-Economic Development as well as alternatives, namely transportation of goods which include cars, trucks, L300 cars, box cars and transportation of passengers that includes public transportations, taxis and rickshaws. Method of analysis used in this study is the Analytical Hierarchy Proccess (AHP). The sample in this research is UPTD. PU CIPTA KARYA Company, The Head of Gisting subdistrict, Secretary of BAPPEDA Tanggamus, Consultant Supervisor and The Village Chief. The results of the research on Economic Analysis of Road Construction in Gisting Subdistrict indicates that acceleration of the economy is the first priority or the most important priority.Based on a test of Alternative Global Priority, that occupies the first priority is the transportation of goods that are supported by the largest contribution from the L300 Cars while the second alternative is the Transportation of Passenger which is supported by the largest contribution from a taxis.